Taxonomy of ’Euconnus complex’. Part XV. Disentangling the Euconnus-Sciacharis knot (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł; Newton, Alfred F. (Zootaxa, 2017)
Many species currently placed in Sciacharis Broun were once included in Euconnus Thomson, and their taxonomic history is complicated due to diffuse and overlapping diagnoses of both genera applied by previous authors, numerous virtually unjustified transfers of species between them, and hundreds of species not assigned to any subgenus. Based on comparative morphological studies of respective type species, we clarify the status of Allomaoria Franz, Austroconophron Franz, Magellanoconnus Franz, Neuraphoconnus Franz and Valdivioconnus Franz. All of them, except for Neuraphoconnus, were originally described as subgenera of Euconnus, later transferred to Sciacharis. Austroconophron is removed from synonymy with Sciacharis s. str. and resurrected as subgenus of Euconnus (resulting in Euconnus (Austroconophron Franz, status rest.); Allomaoria is retained as a junior synonym of Sciacharis s. str.; Magellanoconnus is removed from Sciacharis and restituted as genus (resulting in Magellanoconnus Franz, status rest.); Anthicimimus Franz, previously removed from subgenus of Sciacharis and elevated to genus rank, is reduced to subgenus of Magellanoconnus (resulting in Magellanoconnus (Anthicimimus stat. rev.); Neuraphoconnus is removed from synonymy with Magellanoconnus and resurrected as genus (resulting in Neuraphoconnus Franz, status rest.); and Valdivioconnus is transferred from subgenus of Sciacharis to subgenus of Microscydmus Saulcy & Croissandeau (resulting in Microscydmus (Valdivioconnus Franz, status rev.). The only Australian species of Magellanoconnus is transferred to Kangarooconnus Jałoszyński, gen. n. (resulting in Kangarooconnus carinifrons (Franz), comb. n.). A complete checklist of 302 species and subspecies previously or currently placed in Sciacharis (including 102 restituted and 50 new combinations) is given. Three replacement names are proposed for secondary homonyms resulted from new combinations: Euconnus (Austroconophron) caledonensides Newton, nom. n. (for Euconnus caledonensis Franz, 1986, not Euconnus caledonensis Franz, 1979); Magellanoconnus (s. str.) castrianus Jałoszyński & Newton, nom. n. (for Magellanoconnus castrii (Franz, 1967: 636), not Magellanoconnus castrii (Franz, 1967: 614)); and Sciacharis (Sciacharis) bryantides Newton, nom. n. (for Euconnus bryanti Franz, 1975, not Euconnus bryanti Lhoste, 1939). Lectotypes are designated (des. Jałoszyński) for Euconnus tindoui Franz, 1971, Phagonophana lanosa Broun, 1885, and Neuraphoconnus caledonicus Franz, 1971.